Qualité(s) architecturale(s) des logements sociaux produits par les promoteurs immobiliers : une question qui fait débat - Anne-Laure Jourdheuil (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In order to meet the public authorities’ requests for the quantitative production of social rental housing and for the implementation of social diversity policy, social landlords are required to expand their production methods. Among the production methods developed, the off-plan sale of public housing (VEFA-HLM, Vente en état futur d’achèvement HLM) allows them to acquire new housing from real estate developers in buildings that have not yet been constructed. The development of VEFA-HLM thus contributes to the rapprochement and reconfiguration of the relationships between two worlds of new collective housing production: real estate development and social housing. With that in light, the consequences of the privatization of social rental housing production in terms of architectural quality should be questioned. Although consensus around the definition of architectural quality is far from being reached among researchers and professionals involved in the production of the built environment, or even among inhabitants, it seems very strongly linked to both the spatial and temporal context in terms of the evaluation of this quality. The VEFA-HLM very often allows for the coexistence of private housing and social rental housing within the same operation. However, these housing units built by the same project owner sometimes seem to respond to distinct quality issues. Significant differences can thus be observed between the private and social housing created. In spite of strong criticisms attached to VEFA-HLM, it can be considered as having taken part in opening the debate on the quality of contemporary housing beyond the framework of social housing built by direct contracting authorities.